2021
DOI: 10.3389/feart.2021.784812
|View full text |Cite
|
Sign up to set email alerts
|

Northward Growth of the West Kunlun Mountains: Insight From the Age–Elevation Relationship of New Apatite Fission Track Data

Abstract: The Cenozoic collision between India and Asia promoted the widespread uplift of the Tibetan Plateau, with significant deformation documented in the Pamir Plateau and West Kunlun Mountains. Low-temperature thermochronology and basin provenance analysis have revealed three episodes of rapid deformation and uplift in the Pamir–West Kunlun Mountains during the Cenozoic. However, there is very little low-temperature thermochronology age–elevation relationship (AER) data on fast exhumation events in this area—especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
1
3
0
Order By: Relevance
“…To have the thick Cenozoic deposits, two conditions are necessary, specifically erosion of the uplifted West Kunlun and an endorheic drainage system to accommodate the eroded materials within the southern Tarim Basin. Previous thermochronological investigations revealed that sporadic exhumation may have occurred along South Kunlun by the Paleocene-early Eocence (Cao et al, 2015;Li et al, 2019), consistent with detrital thermochronology and zircon U-Pb geochronological results (Liu et al, 2021;Wang P et al, 2021). Despite sporadic erosion and deposition, the southern Tarim Basin was predominantly formed by deposition of marine facies that were mainly controlled by transgressive and regressive fluctuations of the proto-Paratethys Sea that connected the Tajik Basin and extended to the Mediterranean Tethys to the west (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…To have the thick Cenozoic deposits, two conditions are necessary, specifically erosion of the uplifted West Kunlun and an endorheic drainage system to accommodate the eroded materials within the southern Tarim Basin. Previous thermochronological investigations revealed that sporadic exhumation may have occurred along South Kunlun by the Paleocene-early Eocence (Cao et al, 2015;Li et al, 2019), consistent with detrital thermochronology and zircon U-Pb geochronological results (Liu et al, 2021;Wang P et al, 2021). Despite sporadic erosion and deposition, the southern Tarim Basin was predominantly formed by deposition of marine facies that were mainly controlled by transgressive and regressive fluctuations of the proto-Paratethys Sea that connected the Tajik Basin and extended to the Mediterranean Tethys to the west (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…As oroclinal bending of the MTB mainly occurred after the late Miocene, the maximum sedimentary thickness (D‐N 1 ka) prior to bending along these two profiles was very similar (e.g., nearly 5 km along B‐B’ and ∼4.5 km along C‐C’). This observation contributes to the interpretation of the primarily sublinear E‒W‐trending MTB related to nearly northward compression from the West Kunlun FTBs since the late Miocene (Cao et al., 2015; Li et al., 2007; Liu et al., 2010; Pan et al., 2010; Wang et al., 2011; Yang et al., 2007). The maximum syn‐/postbending sedimentary thickness (N 1 p‒Quaternary) varies (e.g., ∼7 km along B‐B’ and only 4 km along C‐C’).…”
Section: Discussionmentioning
confidence: 77%
“…In addition, this dislocated step more or less corresponds to the southeastern tip of the MTB across the Markit Slope (Figure 1a). The West Kunlun Mountains are long‐lived topographic units that date back to the Triassic–Early Jurassic and were reactivated during the late Oligocene–early Miocene and after the mid‐late Miocene (Arnaud et al., 2003; Cao et al., 2015; Cheng et al., 2017; Jiang & Li, 2014; Li et al., 2007; Liao et al., 2018; Liu et al., 2010). During the northward thrusting of the West Kunlun Mountains over the Tarim Basin to the MTB through the décollement salt‒gypsum layers, this preexisting asymmetric indenter could have triggered dextral transpression at the eastern tip of the MTB (as well as the West Kunlun FTBs and the WKFT) and radial thrusting and strain around the northeastward convex shape of the eastern part of the West Kunlun Mountains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation